2017
DOI: 10.15203/ozp.2388.vol46iss4
|View full text |Cite
|
Sign up to set email alerts
|

Alerters, Critics, and Objectivists: Researchers in Austrian Newspaper Coverage of Climate Change

Abstract: Newspapers are important fora for communicating scientific expertise to the public. Our article asks how researchers convey their expertise and link it to political actions in Austrian newspaper coverage of climate change. Based on researchers' understanding of climate change and the degree of prescriptiveness of their policy recommendations, we identify three positions: alerters, critics, and objectivists. We illustrate how these three types advance different framings of the climate change debate and generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…At the same time, the very content of expert statements on climate change varies depending on the political and cultural context. Expert interventions in the media in many European countries tend to take an alarmist tone in arguing for climate change action, as previous studies have shown in Austria (Hermann et al, 2017), Britain (Schmid-Petri & Arlt, 2016, Germany (Grundmann & Scott, 2014;Taddicken & Reif, 2016), and -especially importantly for our article -Sweden (Berglez et al, 2009). Other contexts have seen a stronger presence of climate change sceptics -for example, in the US (Boykoff, 2013), but also France (Grundmann & Scott, 2014).…”
Section: The Construction Of the Subject Positions Of Experts Ordinar...supporting
confidence: 63%
“…At the same time, the very content of expert statements on climate change varies depending on the political and cultural context. Expert interventions in the media in many European countries tend to take an alarmist tone in arguing for climate change action, as previous studies have shown in Austria (Hermann et al, 2017), Britain (Schmid-Petri & Arlt, 2016, Germany (Grundmann & Scott, 2014;Taddicken & Reif, 2016), and -especially importantly for our article -Sweden (Berglez et al, 2009). Other contexts have seen a stronger presence of climate change sceptics -for example, in the US (Boykoff, 2013), but also France (Grundmann & Scott, 2014).…”
Section: The Construction Of the Subject Positions Of Experts Ordinar...supporting
confidence: 63%
“…At that time, Austria was recognized as an ambitious pioneer in terms of its climate policy [57]. For example, in 1996, Austria established the Austrian Council on Climate Change (ACCC), which is responsible for developing research on the topic of climate change [58]. In phase 2, there were no great advances in terms of the environmental agenda.…”
Section: Climate Policy Trendsmentioning
confidence: 99%